Transformação cística como consequência de terceiro molar inferior incluso - Zanetti, Liliane Scheidegger da Silva; Marano, Renato Rodrigues; Bianchi, Patrícia Roccon; Garcia Júnior, Idelmo Rangel [UNESP]; Barros, Liliana Aparecida Pimenta de (Sociedade Portuguesa de Estomatologia e Medicina Dentaria (SPEMD), 2009)
The permanence of impacted third molar in the jaws can cause many pathological alterations, amongst them the appearance of odontogenic cysts. The paradental cyst appearance and evolution next to a mandibular included third molar was diagnosised in radiograph routine follow-up, and its evolution and treatment are described. Are discussed the aspects related with the preventive removal to the impacted third molars and the necessity to institution a plan of treatment based in clinical history and radiograph in order to establish a preventive protocol the alterations caused by these impactions. The indication of extraction of impacted third enclosed can be a way to preventing the appearance of these and otherspathologies associates to these lesions.
Cyst transformation as consequence of impacted lower third molar
Keywords: Follicle dental; Impacted teeth